Mapping Stunting and Its Risk Factors in Sub-Districts Throughout Semarang City in 2022 - Azizah, Agtika Yasyfa Nur; Ningrum, Dina Nur Anggraini; Wahyuningsih, Siti Endah (Journal of Health Education, 2025)
Background: The prevalence of stunting in Semarang City is the lowest compared to other districts/cities at 10.40%. Semarang City has not used a mapping system in handling stunting cases even though mapping stunting and its risk factors with GIS can help policymakers read areas that can be used as a basis for determining stunting-related programs because each region has different characteristics. Methods: This study combined an ecological study and mapping approach with a cross-sectional design. This research was conducted in 2022. The population in this study were all 16 sub-districts in Semarang City. The sampling technique in this study was total sampling.  Results: The results showed that in the mapping of correlated risk factors, the variables of the percentage of households that have access to safe sanitation,  percentage of households with shared toilet, percentage of LBW, percentage of pregnant women with parity >4, and percentage of pregnant women aged >35 years old were significantly associated with the prevalence of stunting. Conclusions: Sub-districts that can be prioritized for stunting prevention, treatment, and screening are Semarang Selatan, Semarang Utara, Semarang Tengah, Semarang Timur, and Tugu